Decoding Jakarta's Generation Z: An Analysis of Initial Purchase Intention in the Pre-Owned Luxury Bag Sector - Angelina, Angelina; Saffira, Mega; Humolta, Marco Rene; Vinnchi, Chrisielle; Widjaya, Valerie Arielle (MODA, 2024)
In today's consumer landscape, there is a noticeable trend towards exploring different ways of obtaining luxury goods, especially seen in the increasing interest in the pre-owned luxury bags market among Generation Z consumers in Jakarta. This study aims to explore the perceptions of value and risk, product attitudes, and the credibility of authenticity claims regarding the initial purchase intention of pre-owned luxury bags among this demographic. Built upon a thorough examination of current literature and initial exploratory research, an online survey was designed to illustrate the connections among the variables proposed in the conceptual framework.